Endogenous and exogenous polyamines in the organogenesis in Curcuma longa L. - Viu, Alessandra F. M.; Viu, Marco A. O.; Tavares, Armando R.; Vianello, Fabio; Lima, Giuseppina Pace Pereira [UNESP] (Elsevier B.V., 2009)
The present work evaluated the development of different Curcuma longa L. explants (leaves basis, root tips and ancillary buds from rhizome) stimulated by exogenous polyamines, combined with naphtalenacetic acid (NAA) or with 6-benzyl-aminopurine (BAP), to produce callus and its Subsequent differentiation. The explants, isolated from field plants, were previously subjected to a basic cleaning method and were inoculated onto Murashige and Skoog culture medium (MS) [Murashige, T.S., Skoog, F., 1962. A revised medium for rapid growth and bioassays with tobacco tissue culture. Physiologia Plantarum 15, 473-497] supplemented with NAA (2.0 mg L(-1)). Buds were subjected to different treatments, with or Without 5.0 and 10.0 mmol L(-1) exogenous polyamines (mixture of putrescine:spermine:spermidine, 1: 1: 1) combined with NAA. The calluses obtained were transferred into the same medium, supplemented with the mixture of polyamines combined with BAP, in order to induce plant differentiation. For C longa, buds were the most efficient explants for callus induction (p < 0.05). The application of exogenous polyamines (5.0 and 10.0 mmol L(-1)) produced the most developed Callus, With numerous roots. The medium Supplemented with 10 mmol L(-1) polyamine mixture, combined with BAP, induced good regeneration, producing vigorous plants and excellent shoot formation. Polyamines addition promoted the formation of callus, roots and leaves, representing an important factor in the determination of indirect organogenesis in C longa L., and putrescine content may be considered a valuable marker of the differentiation process in this specie, as well as the enzyme peroxidase. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: Organogenesis; Putrescine; Spermidine; Spermine; Peroxidase